Three lessons from government spending and the post-pandemic recovery - Pavlina R. Tcherneva (Levy Economics Institute of Bard College, 2024)
The central lesson of the COVID-19 fiscal response is that money is not scarce. Without delay, governments around the world appropriated budgets that dwarfed any other postwar crisis policy. In 2020, Japan passed a stimulus package equal to 54.8 percent of GDP, while in the U.S., it was equivalent to 26.9 percent and in Canada to 20.1 percent. Italy, France, and Germany spent 10.1, 10.4, and 10.7 percent of GDP, respectively.
Keywords: 330; COVID-19; Economic recovery; Government expenditure; Pandemics